PENGARUH LAMA PERENDAMAN AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum. L) PADA BERBAGAI MACAM MEDIA - Ramdhani, Fendi (VIABEL: Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2019)
Demand for shallots continues to increase due to increasing population and consumption of mera onions. This research was carried out in jingglong village, Sutojayan sub-district, Blitar district in April - June 2018. This research was conducted using factorial randomized block design (RBD) with 2 factors, the first factor was immersion in coconut water (k) which consisted of 3 levels namely immersion for 1 hour (k1) soaking for 2 hours (k2) soaking for 3 hours (k3). The second factor is various media (m) consisting of 3 levels: soil 1: fertilizer 1: husk ash 1 (m1), soil 2: fertilizer 1: husk ash 1 (m2), soil 1: fertilizer 2: husk ash 1 ( m3) The variables observed included plant height, number of shoots, number of leaves, weight of tuber stover, wet weight of tubers, dry weight of tubers. Data were analyzed using analysis of variance (ANOVA) level of 5% and further testing with Duncan’s Multiple Range Test (DMRT). There is no real interaction between coconut water immersion and various planting media on the growth and yield of shallots. The treatment of coconut water immersion (k) significantly affected the height of shallot plants at the age of 14 days and 21 days, and affected the number of shoots and leaves at all ages of observation. The treatment of various planting media showed a significant difference at the age of 14 days to 21 days. The treatment of various planting media had a significant effect on the weight of stover and the wet weight of onion tubers with the highest yield (m1) of 122.03 gr, while in the wet weight the highest yield was on media (m1) with a yield of 80.51 gr.